Analisis Spektrum Akustik Tangis Bayi Penderita Penyakit Jantung Bawaan menggunakan Teknik Dynamic Time Warping: Hana Afifah, Iwan Yahya, Nuryani, Harjana - Hana Afifah, Hana Afifah; Iwan Yahya, Iwan Yahya; Nuryani, Nuryani; Harjana, Harjana (Jurnal Fisika dan Aplikasinya, 2025)
This paper emphasizes on acoustics spectral similarity analysis on of normal infant cry compared to infant spectrum with Congenital Heart Disease (CHD). Ten of the cries signals of infant with CHD and normal baby aged less than a month were recorded by using Sony IC-Recorder ICD-PX333. The Speech Filing System software utilized for estimating fundamental frequency, formants, and MFCCs were used as cry spectral characteristics to be visualized using Dynamic TimeWarping (DTW) technique. The result shows that both group partially has significant different characteristics since anomalies occurred which is considered due to the intersection on the values of fundamental frequency and formants of the both groups.